2016
DOI: 10.1097/brs.0000000000001290
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Rehabilitation Intervention for Low Back Pain in Randomized Controlled Trials

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
3
10
0
1
Order By: Relevance
“…While neither intervention was adequately reported, the control group was more likely to be underreported as compared to the intervention group, despite both containing exercise components. These findings are fairly consistent with recent literature which suggests less than one fifth of studies adequately report exercise interventions in other musculoskeletal conditions, [ 132 ] educational interventions, [ 133 ] as well as in the intensive care unit [ 134 ]. Additionally, previous studies have shown that reporting of interventions has improved with time in other health conditions [ 132 ]; however, the results of this study show no differences in reporting of interventions over time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While neither intervention was adequately reported, the control group was more likely to be underreported as compared to the intervention group, despite both containing exercise components. These findings are fairly consistent with recent literature which suggests less than one fifth of studies adequately report exercise interventions in other musculoskeletal conditions, [ 132 ] educational interventions, [ 133 ] as well as in the intensive care unit [ 134 ]. Additionally, previous studies have shown that reporting of interventions has improved with time in other health conditions [ 132 ]; however, the results of this study show no differences in reporting of interventions over time.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are fairly consistent with recent literature which suggests less than one fifth of studies adequately report exercise interventions in other musculoskeletal conditions, [ 132 ] educational interventions, [ 133 ] as well as in the intensive care unit [ 134 ]. Additionally, previous studies have shown that reporting of interventions has improved with time in other health conditions [ 132 ]; however, the results of this study show no differences in reporting of interventions over time. This suggests a significant proportion of researchers assessing post-operative TKA interventions have not adapted the newer recommendations for reporting of interventions.…”
Section: Discussionsupporting
confidence: 90%
“…In the literature, disability and pain are the most frequently investigated outcomes in lowback pain rehabilitation: several authors have recommended including these measurements in the back-specific core outcome sets because they are most relevant to patients, health care practitioners, regulators, industry representatives, and policy-makers 28 . They were also the elective outcome measures most often used in RCTs according to our and a recent review which found a low frequency of reporting outcome and intervention descriptions, reflecting a multidimensional lack of quality in rehabilitation RCTs 29 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is a common problem of complex non-pharmacological interventions [55, 56]. Potential issues of the proposed review include high clinical heterogeneity, poor quality of reporting of the included trials, and difficulty in interpreting measures of effect when the pooled estimates come from trials that measured the outcome using different measurement tools [35, 57]. Another plausible limitation, solely concerning the network meta-analysis, might be the lack of available treatment comparisons to build robust nodes.…”
Section: Discussionmentioning
confidence: 99%
“…We will include them since they could be clinically relevant for LBP stakeholders and there is sparse evidence of their efficacy for acute LBP in the literature [22, 2931]. We will extract sufficient and important intervention details as suggested by the TIDieR checklist [32] in order to create consistent nodes [3335]. Thus, we will set the following classification of interventions for potential nodes:Biopsychosocial rehabilitation (including cognitive behavioral treatment and back school)Exercise (e.g., resistance or aerobic training)Manual therapy (e.g., spinal manipulation, mobilization, trigger point/myofascial therapy)Dry needling and acupunctureEducation (e.g., booklet)Any physical therapy (e.g., low-laser therapy, diathermy, transcutaneous electrical nerve stimulation, ultrasound therapy, heat wrap)Taping (e.g., kinesiotaping)Usual care defined as treatment suggested by general medicine (minimal intervention: advice to stay active or to take drugs as needed)ParacetamolNon-steroidal anti-inflammatory drugs (NSAIDs), including COX-2 inhibitorsMuscle relaxant drugsOpioid drugsSteroidsAntidepressant drugsInert treatment (e.g., placebo drug, sham therapy)No treatment (no treatment, waiting list control)…”
Section: Methodsmentioning
confidence: 99%